Evaluation of Outcomes in Chest Trauma Patients using Chest Trauma Scoring System - Mahaseth, Rahul; Shah, Santosh; KC, Rajkumar (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Chest trauma is a common surgical incidence all over the world. Chest Trauma scoring system (CTS) is found in many studies to be an effective tool to predict outcomes in chest trauma patients. The need for a universal system for thoracic trauma is justiﬁed to identify critical factors, to predict patient outcomes, urgent need for intervention, and requirement of intensive care and to communicate with the family. Therefore there is a need of study and scoring system which can predict possible outcome. MATERIAL AND METHODS This is a prospective, longitudinal, observational study conducted at Universal College of Medical Sciences, Bhairahawa from October 2019 to March 2021. The chest trauma score was used to evaluate the outcome in patient admitted with blunt trauma chest. Duration of hospital stay, respiratory complications, need of ICU and Ventilators and mortality were noted as outcomes. RESULTS In this study, 79 cases with blunt trauma chest were admitted with road trafﬁc accident being major factor for admission. Most patients were in age group 45-65 years of age with male predominance (84.8%). The results showed that patient with high CTS ≥5 was associated with higher incidence of pneumonia and need of ICU. The ROC curve showed that CTS predict signiﬁcantly mortality with sensitivity of 100% and speciﬁcity of 92.2% with cutoff value of 7.5. Similarly, mean duration of hospital stay of patients having CTS ≥5 was 6.57 days more than patients having CTS <5. CONCLUSION Chest Trauma Score is a good predictor of outcome in patient with blunt chest trauma.